(untitled) (Journal of Applied Learning and Teaching, 2020)
Student retention is a key strategic issue in higher education affecting student experience, university funding, and reputation. It is critical for institutions to identify factors that impact upon student success, build effective strategies to enhance student outcomes, and respond to the emerging evidence-base of distance student engagement. The University of Tasmania has one of the highest attrition rates in Australia, at 28 percent for commencing bachelor students. Studying by distance is a known risk factor affecting attrition and it is vital that we understand the challenges that ‘at risk’ distance students face when they engage in higher education and how to best support them for success. This study describes a Community of Practice approach that identified four key challenges to reduce student attrition in online degree programs: (i) the importance of knowing your students, (ii) the difficulty in getting reliable data, (iii) the need for ‘belonging’ for online students and early, meaningful engagement, and (iv) student access to known academics. With no magic bullet to reduce student attrition rates, we present a range of targeted and connected early interventions designed to support students to succeed and enhance their learning experience.